2018
DOI: 10.1002/ame2.12023
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of islet β‐cells in tree shrews and rats

Abstract: Backgroud: Current understanding of injury and regeneration of islet β-cells in diabetes is mainly based on rodent studies. The tree shrew is now generally accepted as being among the closest living relatives of primates, and has been widely used in animal experimentation. However, there are few reports on islet cell composition and regeneration of β-cells in tree shrews. Methods:In this study, we examined the changes in islet cell composition and regeneration of β-cells after streptozotocin (STZ) treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This route of insulin secretion is impaired by reduced levels of adenosine triphosphate (ATP). This occurs because STZ interferes with the expression of GLUT2 and the citric acid cycle, reducing the production of nicotinamide adenine dinucleotide (NAD) and ATP below physiological levels (Zhao et al 2018). Thus, oxygen consumption in mitochondria decreases substantially, resulting in the formation of superoxide anions, and increased activity of the enzyme xanthine oxidase (Turk et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…This route of insulin secretion is impaired by reduced levels of adenosine triphosphate (ATP). This occurs because STZ interferes with the expression of GLUT2 and the citric acid cycle, reducing the production of nicotinamide adenine dinucleotide (NAD) and ATP below physiological levels (Zhao et al 2018). Thus, oxygen consumption in mitochondria decreases substantially, resulting in the formation of superoxide anions, and increased activity of the enzyme xanthine oxidase (Turk et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…However, in this experiment, the severe DM model induced DKA even though in the exogenous insulin treatment, making intra-islet regeneration of beta cells unlikely. Additionally, although alpha-to-beta cell conversion is considered possible, it was not observed histopathologically over a 21-day period in a high-dose STZ model (60 mg/kg) in rats, instead, this research team histopathologically confirmed that regeneration primarily occurred from centroacinar exocrine cells [ 20 ]. However, from a functional perspective, BGLs remained high after STZ administration, and there was no significant increase in blood insulin levels.…”
Section: Discussionmentioning
confidence: 99%